El derecho de intervención humanitaria en la globalización y el conflicto de los Grandes Lagos - Palomo Garrido, Aleksandro (El Colegio de México A.C., 2014)
Armed intervention under the auspices of the UN in dealing with international conflicts was a rarely used practice during the Cold War, as it undermined national sovereignty. Criticism that treated them as covert imperial interference enabling expansion of the great powers delegitimized them in the eyes of the international community. Meanwhile, the radicalization of the confrontation between the USSR and the US blocked any decision by the Security Council, as both held a veto. However, with the collapse of the USSR and the arrival of the age of globalization, recourse to the right of humanitarian intervention acquired new relevance. The article focuses on the Great Lakes conflict between 1994-2010.